Why science gets cut out of policy - Bergin, Anthony (New Zealand Science Review, 2018)
​Science has an important role to play in influencing decision-making in international and national forums. But do scientists understand how it needs to be delivered, or what’s required from science for the development of policy and achieving consensus? And do they know what constitutes a solution that a policymaker can use?The extent to which scientific knowledge gets traction in policy will depend partly on the state of science knowledge on the issue, and partly on the degree of controversy surrounding the issue under consideration. It will also depend on the degree of public and political attention the matter gets.